Guidelines for Economic Analysis of Power Sector Projects : Renewable Energy Projects - World Bank (Washington, DC, 2015)
These guidelines are directed to the economic analysis of power sector policy analysis and the appraisal of power sector investment projects. The general guidance is complemented by an Annex Volume that contains relevant technical notes, a glossary, and an extended Bibliography. In this first edition, the focus of the technical notes is on grid-connected renewable energy projects. In FY16 the scope of the technical notes will be extended to cover transmission & distribution, rural electrification, off-grid, energy efficiency, and thermal projects.